2020
DOI: 10.1101/2020.01.17.910810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modular slowing of resting-state dynamic Functional Connectivity as a marker of cognitive dysfunction induced by sleep deprivation

Abstract: Highlights• Sleep Deprivation (SD) slows down the random walk in FC space implemented by Dynamic Functional Connectivity (dFC) at rest.• Whole-brain level slowing of dFC speed does not selectively correlate with fine and taskspecific changes in performance • We quantify dFC speed separately for different functional sub-networks coordinated by distinct regional "meta-hubs"• Modular dFC speed variations capture subtle and task-specific variations of cognitive performance induced by SD. Keywords Dynamic Functiona… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…A similar situation can be occurring at the connectome level, and the s-core decomposition is a first step toward the description of this kind of structural high-order interactions. A question for future research is whether the functional high-order interactions-as the one revealed by non-trivial "meta-connectivity", constraining fluctuations of pairwise resting state functional links [44]are related to the core-shell organization.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation can be occurring at the connectome level, and the s-core decomposition is a first step toward the description of this kind of structural high-order interactions. A question for future research is whether the functional high-order interactions-as the one revealed by non-trivial "meta-connectivity", constraining fluctuations of pairwise resting state functional links [44]are related to the core-shell organization.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of a variety of dynamic regimes from changes in the global 'environmental' parameters is biologically realistic. For example, sleep deprivation is associated with changes in the speed of the F C evolution [72]. Accordingly, distinct features of the dF C should correspond to a di↵erent underlying neuroelectric organization (and perhaps to distinct mechanisms of communication across the brain regions [73]).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the extraction of ERP templates in our case depended on a manual inspection, but more sophisticated algorithms for the temporal clustering of single-trial ERP topographies(Vahid et al, 2020) could be used and combined with our variability analyses schemes. The occurrence of large within-trial variations also need to be put in correspondence with microstate transitions or other approaches to describe ongoing dynamics of intrinsic functional connectivity(Lombardo et al, 2020) which also reveal power-law distributed statistics of fluctuations. Finally, linking activity to network state dynamics may allow assessing whether exchange of information is dominated by bottom-up or top-down flows at different ages or ERP stages(Bastos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%